Islamic Financial Technology Sentiment Analysis: A SentiStrength Application - Anisa; Lina Marlina (Ekonomi Islam Indonesia, 2022)
This research was conducted to examine Islamic Financial Technology in the scope of the economy in terms of scientific research in journals published and indexed by Scopus. The method used is sentiment analysis from secondary data in the form of 66 journals published in the last five years and then processed using Ms. software. Excel 2016 and SentiStrength. The results showed that Islamic Financial Technology in the scientific literature has increased. The results of the sentiment analysis show that there is a tendency for a neutral perception in the scientific literature towards Islamic Financial Technology, with a neutral sentiment of 53%. Then followed by negative sentiment by 24%. Then the positive sentiment whose results are not much different from the negative sentiment, namely the positive sentiment of 23%. The benefit of this research is for literature material and considerations related to Islamic Financial Technology. As well as efforts to find out the threats, negative perceptions, and shortcomings of Islamic Financial Technology. In addition, to find out positive perceptions, advantages and benefits of Islamic Financial Technology.